2019
DOI: 10.1038/s41598-019-43100-1
|View full text |Cite
|
Sign up to set email alerts
|

A gapmer antisense oligonucleotide targeting SRRM4 is a novel therapeutic medicine for lung cancer

Abstract: Small cell lung cancer (SCLC) is the most aggressive neuroendocrine phenotype of the deadliest human lung cancers. However the therapeutic landscape for SCLC has not changed in over 30 years. Effective treatment and prognosis are needed to combat this aggressive cancer. Herein we report that Ser/Arg repetitive matrix 4 (SRRM4), a splicing activator, is abnormally expressed at high levels in SCLC and thus is a potential therapeutic target. We screened an effective gapmer antisense oligonucleotide (gASO) targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Remarkably, we found that SRRM4 was the only SF significantly upregulated in NFPTs, which was also associated with higher chiasmatic compression. These results compare nicely with the overexpression of SRRM4 reported in small cell lung cancers and in neuroendocrine prostate cancers, where SRRM4 was also correlated with poor patient survival [56,57].…”
Section: Discussionsupporting
confidence: 82%
“…Remarkably, we found that SRRM4 was the only SF significantly upregulated in NFPTs, which was also associated with higher chiasmatic compression. These results compare nicely with the overexpression of SRRM4 reported in small cell lung cancers and in neuroendocrine prostate cancers, where SRRM4 was also correlated with poor patient survival [56,57].…”
Section: Discussionsupporting
confidence: 82%
“… 18 Therefore, nucleic acid drugs potentially serve as a better approach to targeted therapy than therapeutic antibodies. The strengths of our AmNA-ASOs are as follows: (1) oligonucleotide sequences with enhanced target specificity, lack of significant homology with the mouse counterpart of SYT13 , and minimal toxicity; (2) chemical modifications extend the half-life of therapeutic ASOs to prolong exposure of tumors on the peritoneal wall; 8 , 32 (3) higher binding affinity to target molecules that enhance drug efficacy; 33 and (4) chemical modifications that change the lipophilicity of ASOs to confer resistance to absorption in the peritoneal cavity. 7 , 34 The two ASOs studied here were carefully selected from 71 sequences through multistep screening for high knockdown efficacy, effective in vitro activity, and potentially minimal off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…ASOs used to treat various disorders are in different phases of clinical trials, and some nucleic acid drugs are approved for treating retinitis, homozygous familial hypercholesterolemia, and Duchenne muscular dystrophy. 8 , 11 , 32 However, over the past two decades, ASO-based cancer therapy has been unsuccessful despite substantial efforts directed toward developing rational oligonucleotide strategies to silence gene expression. 7 , 32 Vulnerability to endogenous nucleases, poor delivery to solid cancer tissues, and insufficient disease specificity of the target molecules represent serious obstacles to the clinical use of ASOs.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-4516, located in the cytoplasm,23 has important regulatory functions in multiple pathological conditions, such as HIV-associated neurocognitive disorder, thyroid carcinomas and lung cancer 24–26. Meanwhile, some targets and signalling pathways may underlie miR-4516-mediated functions.…”
Section: Discussionmentioning
confidence: 99%